Optical Methods in Biology and Medicine электронный курс - Губарев, Ф. А. специалист в области электроники доцент Томского политехнического университета, кандидат физико-математических наук 1979- (TPU Moodle, 2017)
The course "Optical Methods in Biology and Medicine" has been developed in support of the same discipline "Optical Methods in Biology and Medicine" and is devoted to the study of basic principles of light propagation and interaction with biological tissues, as well as optical devices for medical diagnostics and investigation of fundamental properties of bioobjects. In this course, the features of the functioning and application of physical methods of research, such as visual diagnostics, spectroscopy, and tomography are considered. Much attention in the course is paid to the practical application of optical methods and devices.